SISTEM PELAYANAN E-MEDIC POLIKLINIK RAWAT JALAN PADA RSUD BAYUNG LENCIR - Aidil Afriansyah; Ermida Silitonga (Jurnal TIPS : Jurnal Teknologi Informasi dan Komputer Politeknik Sekayu, 2016)
Obstetrics Polyclinic as outpatient medical care units in General Hospital Bayung Lencir, has the highest number of clinic visits other, thus causing the transaction processes of medical services increasingly complex. These processes are difficult to be met with a manual system. It is necesarry to change a computerized system of medical care. This research contained about the e-medic software at Obstetrics Polyclinic of General Hospital Bayung Lencir. Overall, e- medic software will help the processes of medical services transactions, provide data security of medical records for ongoing medical care, facilitate the retrieval of medical records and income information quickly and precisely match the needs of users.